Pengaruh Fatherless terhadap Akhlak Anak dalam Kajian Hukum Keluarga Islam - Laman, Ilham; Ma'ruf, Muh. Azhar; Sakka, Rahman; Meidiyansyah, Wahyu (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2023)
This research aims to examine the influence of fatherlessness (the absence of a father) on children's moral conduct from the perspective of Islamic family law. Fatherlessness is a phenomenon where a child does not have an actively involved father in their life. In Islam, the family is an important institution that provides a strong foundation of morals and ethics to children. The research method employed is a qualitative approach, utilizing documentary analysis, literature review, and interviews with experts in Islamic family law. Through this research, it is expected to gain a better understanding of the impact of fatherlessness on children's moral conduct within the context of Islamic family law. The findings of the research indicate that the presence of a father in the family plays a crucial role in shaping children's moral conduct. The father serves not only as an economic provider but also as a moral guide and authoritative figure who imparts religious education and Islamic values to the children. The presence of a father can influence the attitudes, behaviors, and overall moral understanding of the children. Furthermore, fatherlessness can also lead to an imbalance in the formation of a child's identity. Children without the presence of a father often struggle to develop their sense of self and find their proper roles in society. This can have negative implications for their moral conduct, such as a lack of responsibility, a tendency to engage in negative behaviors, and deficiencies in social skills. In the context of Islamic family law, this research also explores the concept of paternal responsibilities in educating children, as well as the family's responsibility in creating an environment supportive of positive moral development. The research identifies several potential solutions to address the issue of fatherlessness, such as the establishment of father mentoring programs, family empowerment initiatives, and active community involvement in supporting incomplete families Keywords: Fatherlessness, Children's Moral Conduct, Islamic Family Law, Role of Father, Negative Influence